2015
DOI: 10.1007/lrsp-2015-2
|View full text |Cite
|
Sign up to set email alerts
|

The FIP and Inverse FIP Effects in Solar and Stellar Coronae

Abstract: We review our state of knowledge of coronal element abundance anomalies in the Sun and stars. We concentrate on the first ionization potential (FIP) effect observed in the solar corona and slow-speed wind, and in the coronae of solar-like dwarf stars, and the "inverse FIP" effect seen in the corona of stars of later spectral type; specifically M dwarfs. These effects relate to the enhancement or depletion, respectively, in coronal abundance with respect to photospheric values of elements with FIP below about 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
304
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(340 citation statements)
references
References 306 publications
(502 reference statements)
19
304
3
Order By: Relevance
“…For example, the O +7 /O +6 ratio > 1.0 (e.g., Henke et al 2001), and average iron charge states > 12 (e.g., Lepri et al 2001) are good signatures of the ICME-plasma. On the other hand, the elemental ratios depend, in a complex way, on chromospheric temperatures, the magnetic field configuration at the origin of the plasma, and the plasma confinement time before the release (e.g., Laming (2015), and references therein). In ICMEs, increased amounts of high charge states of elements such as Fe, Ne, Si, Mg are often observed suggesting extended confinement times (e.g., Lepri et al 2001;Zurbuchen et al 2016).…”
Section: General Icme Signaturesmentioning
confidence: 99%
“…For example, the O +7 /O +6 ratio > 1.0 (e.g., Henke et al 2001), and average iron charge states > 12 (e.g., Lepri et al 2001) are good signatures of the ICME-plasma. On the other hand, the elemental ratios depend, in a complex way, on chromospheric temperatures, the magnetic field configuration at the origin of the plasma, and the plasma confinement time before the release (e.g., Laming (2015), and references therein). In ICMEs, increased amounts of high charge states of elements such as Fe, Ne, Si, Mg are often observed suggesting extended confinement times (e.g., Lepri et al 2001;Zurbuchen et al 2016).…”
Section: General Icme Signaturesmentioning
confidence: 99%
“…FIP biases of the order 1.0 are representative of photospheric plasma, whereas FIP biases of the order of 2 -3 correspond to coronal plasma composition (for a review of the FIP effect including the interpretation of FIP biases, see Laming, 2015). Therefore, these values both suggest plasma that is coronal in composition rather than photospheric.…”
Section: Plasma Compositionmentioning
confidence: 99%
“…It has long been observed that some solar TR and coronal features show variations in the chemical abundances, which are correlated with the first ionization potential (FIP) of the element (see, e.g., Laming 2015). The low-FIP (≤ 10 eV) elements are more abundant than the high-FIP ones, relative to the photospheric values (the FIP bias).…”
Section: Chemical Abundancesmentioning
confidence: 99%